Distantly Reading Dante Translations - Blakesley, Jacob (Vertimo studijos, 2017)
[full article, abstract in English; abstract in Lithuanian] This paper outlines a new research project that aims to catalogue and investigate all booklength translations of Dante’s Divine Comedy in 100 countries. This will be, in fact, the first project to map the circulation and translation of Dante’s Commedia across the globe using statistics and analysis. Despite 700 years of Dante Studies, there still exists no comprehensive bibliography of translations; and critical studies still focus primarily on major languages, neglecting less-translated languages. The theoretical background of this project draws on Franco Moretti’s ‘distant reading’, David Damrosch’s theories of world literature, and Johan Heilbron’s world system of translations. This project will include three strands, which it aims to carry out with a team of scholars. The first will examine the empirical data about the translations of the Commedia and their circulation abroad. The second strand will study the formal aspects of the translations, seeing where the Commedia was translated into terza rima, and discovering the predominant metrical forms of translations across the world. The third strand will investigate how the Commedia was translated under censorship, in fascist regimes, theocracies, military dictatorships, constitutional monarchies, the Eastern Bloc and Communist dictatorships. As the project is still in the early stages of research I will not be giving conclusions, but rather suggesting new pathways for future development.